2013
DOI: 10.1371/journal.pone.0062013
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Delay of Status Epilepticus Onset in an In Vivo Rodent Epilepsy Model

Abstract: Epilepsy is a devastating disease, currently treated with medications, surgery or electrical stimulation. None of these approaches is totally effective and our ability to control seizures remains limited and complicated by frequent side effects. The emerging revolutionary technique of optogenetics enables manipulation of the activity of specific neuronal populations in vivo with exquisite spatiotemporal resolution using light. We used optogenetic approaches to test the role of hippocampal excitatory neurons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 42 publications
0
34
2
1
Order By: Relevance
“…Thus, synaptic vesicles could represent an important and critical target for the prevention of aberrant action potentials and hyperactivity in patients with epilepsy. Recent progress to suppress epilepsy and seizures has emphasized the use of various light-or chemicalgated channels expressed in different neurons and circuits within the brain (Tønnesen et al 2009;Sukhotinsky et al 2013;Kätzel et al 2014). While these show great promise, the problems with these types of manipulations in human patients will be halted by the ability to safely perform genome editing in human tissues, a significant technological challenge.…”
Section: Synaptic Vesicles and Epilepsymentioning
confidence: 99%
“…Thus, synaptic vesicles could represent an important and critical target for the prevention of aberrant action potentials and hyperactivity in patients with epilepsy. Recent progress to suppress epilepsy and seizures has emphasized the use of various light-or chemicalgated channels expressed in different neurons and circuits within the brain (Tønnesen et al 2009;Sukhotinsky et al 2013;Kätzel et al 2014). While these show great promise, the problems with these types of manipulations in human patients will be halted by the ability to safely perform genome editing in human tissues, a significant technological challenge.…”
Section: Synaptic Vesicles and Epilepsymentioning
confidence: 99%
“…Indeed, since fast ripples are thought to reflect the abnormal synchronous firing of principal cells, independent of inhibitory neurotransmission (Bragin et al, 1999(Bragin et al, , 2011Dzhala and Staley, 2004;Foffani et al, 2007;Ibarz et al, 2010), we are inclined to speculate that SE depends on the preponderant activation of pyramidal cell (glutamatergic) networks. In line with this hypothesis, it has been reported that the inhibition of hippocampal pyramidal neurons in the lithium-pilocarpine model delays the onset of SE (Sukhotinsky et al, 2013). Perforant-path stimulation also induces a SE that is dependent on the activity of NMDA receptors (Wasterlain et al, 2000).…”
Section: High-frequency Oscillations During Ictal and Post-ictal Periodsmentioning
confidence: 74%
“…1). Similarly, seizure inhibition has been achieved using optogenetics in both acute models (including acute systemic lithium-pilocarpine in rat 23 and acute intrahippocampal bicuculline methiodide 24 or 4-Aminopyridine 25 in mouse) and chronic models (including stroke-induced thalamocortical epilepsy in rats 16 , tetanus toxin model of focal neocortical epilepsy in rat 26 , and intrahippocampal kainate model of temporal lobe epilepsy in mouse 18,27 ) (Fig. 2), in addition to inhibiting epileptiform activity in slices 24,28 and in silico 29 .…”
Section: Specificity Is Key To Unlocking Icto- and Epileptogenesismentioning
confidence: 99%